Virtual reality to promote wellbeing in persons with dementia: A scoping review. (21st December 2021) - Appel, Lora; Ali, Suad; Narag, Tanya; Mozeson, Krystyna; Pasat, Zain; Orchanian-Cheff, Ani; Campos, Jennifer L
Virtual Reality (VR) technologies have increasingly been considered potentially valuable tools in dementia-related research and could serve as non-pharmacological therapy to improve quality of life (QoL) and wellbeing for persons with dementia (PwD). In this scoping review, we summarize peer-reviewed articles published up to Jan-21, 2021, on the use of VR to promote wellbeing in PwD. Eighteen manuscripts (reporting on 19 studies) met the inclusion criteria, with a majority published in the past 2 years. Two reviewers independently coded the articles regarding A) intended clinical outcomes and effectiveness of the interventions, B) study sample (characteristics of the participants), C) intervention administration (by whom, what setting), D) experimental methods (design/instruments), and E) technical properties of the VR-systems (hardware/devices and software/content). Emotional outcomes were by far the most common objectives of the interventions, reported in seventeen (89.5%) of the included articles. Outcomes addressing social engagement and personhood in PwD have not been thoroughly explored using VR. Based on the positive impact of VR, future opportunities lie in identifying special features and customization of the hardware/software to afford the most benefit to different sub-groups of the target population. Overall, this review found that VR represents a promising tool for promoting wellbeing in PwD, with positive or neutral impact reported on emotional, social, and functional aspects of wellbeing.